Colon cancer presenting as an abdominal wall abscess: a case report - Hernández, Marco A.; Garza, Jorge A.; González, Gabriel G.; Cabrera, Diego R. (International Journal of Research in Medical Sciences, 2025)
Colorectal cancer is one of the most common malignancies worldwide. However, its initial presentation as an abdominal wall abscess is extremely rare, occurring in only 0.3% to 4% of cases. Such atypical presentations may delay diagnosis and treatment, increasing morbidity. We present the case of a 58-year-old male with a history of comorbidities and chronic alcohol use. He developed progressive right flank swelling and localized pain following blunt trauma. Clinical evaluation and contrast-enhanced CT imaging revealed a cecal mass with infiltration into adjacent muscles and a purulent collection. The patient underwent CT-guided drainage followed by open debridement. Colonoscopy and biopsy confirmed adenocarcinoma and a right hemicolectomy with lymphadenectomy was performed. Histopathological analysis revealed a poorly differentiated adenocarcinoma pT4bN1M0, with infiltration into the appendix, ileum and pericolonic tissues, as well as angiolymphatic and perineural invasion. One of 27 lymph nodes was positive for metastasis. Postoperative recovery was uneventful and the patient was referred for adjuvant chemotherapy. Although rare, colorectal cancer should be considered in the differential diagnosis of patients presenting with abdominal wall abscesses, especially when risk factors or systemic symptoms are present. Cross-sectional imaging and colonoscopy are critical for early identification. Timely surgical intervention and oncologic resection with adequate lymphadenectomy significantly improve prognosis. This case highlights the importance of recognizing unusual manifestations of colorectal cancer to avoid delays in diagnosis and optimize patient outcomes.